Immigration trends, consequences and prospects for the United States - Chiswick, Barry R. (Emerald, 2007)
Immigration to what is now the United States has been a contentious issue from the earliest days of the European settlement. The tension between those opposing further immigration on either social or economic grounds and those favoring it has continued over these 3 1/2 centuries to this very day. The complexity of the immigration debate has intensified over the past few decades because of changes in the role of the United States in the international arena, changes in the way Americans view themselves, and changes in the U.S. economy. The growth of the role of government in providing medical, educational and income transfer benefits (in kind and in cash), especially to low-income families has implications for the impacts on the U.S. economy of low-skilled immigrants.The change in the structure of the economy, from a growing demand for production workers in factories and mines to an economy with a declining demand in these sectors but a high demand for workers with high levels of technical and managerial skill, also has implications for immigration policy. In this complex environment, immigration policy has again risen to the forefront. What has been recent immigration history and what have been the consequences of these inflows of people? The purpose of this volume is to address these contemporary issues.
Keywords: Social Science -- Emigration & Immigration.; Economics.; Labor economics.; elektronické knihy; electronic books